Pengaruh Edukasi Gizi Menggunakan Media Terhadap Peningkatan Pengetahuan dalam Upaya Pencegahan Obesitas pada Remaja di MTs Al-Khairiyah - Arunisa Rahian Fadila; Ratih Kurniasari (LPPM Universitas Respati Indonesia, 2022)
Obesity is a problem that worries adolescents. Obesity can occur due to consumption patterns and wrong food selection behavior, resulting in an imbalance between nutritional intake and nutritional adequacy. This study aims to determine the effect of nutrition education using leaflets and animated videos on increasing knowledge in preventing obesity in adolescents at MTs Al-Khairiyah. This type of research is a quasi-experimental with a pretest-posttest design. The research sample amounted to 40 respondents with 20 respondents in each treatment group. The results showed an increase in the average value of nutritional education knowledge in the leaflet group from before 11.60 to 13.95 and in the animation video group from before 10.80 to 14.25. There was a difference in the average value of nutritional education knowledge in the leaflet and animated video groups (p<0.05). It can be concluded that nutrition education using leaflets and animated videos has an effect on increasing knowledge in efforts to prevent obesity in adolescents.